2004
DOI: 10.1007/s00228-004-0820-6
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin effect on high-density lipoprotein-associated paraoxonase activity and oxidative DNA damage

Abstract: These findings show that atorvastatin treatment favorably affected the lipid profile, increasing the activity of HDL-associated PON and decreasing the cytotoxic effect of oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
48
3
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 38 publications
9
48
3
4
Order By: Relevance
“…These results suggest that these genotypes are not associated with physiological responses to atorvastatin, which has been observed by others [8,16]. However, we found that the PON1 T(-107)C polymorphism significantly influences the levels of oxidative stress parameters after atorvastatin treatment, which is in contrast with a previous report [41].…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…These results suggest that these genotypes are not associated with physiological responses to atorvastatin, which has been observed by others [8,16]. However, we found that the PON1 T(-107)C polymorphism significantly influences the levels of oxidative stress parameters after atorvastatin treatment, which is in contrast with a previous report [41].…”
Section: Discussioncontrasting
confidence: 96%
“…Atorvastatin is a drug of choice for reducing lipids in hypercholesterolemic patients. Many studies have demonstrated that atorvastatin induces a significant reduction in total cholesterol, LDL-C, and triglycerides levels, but the effect of atorvastatin on HDL-C remains unchanged [16,20,31,36,41]. Similarly to previous studies, we found that atorvastatin significantly reduces total cholesterol (24.5%), LDL-C (25.4%) and triglyceride (24.4%) levels; however, there were insignificant changes in HDL-C levels.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…PON1 activity was increased inversely proportionally to decreased lipid peroxides caused by ROS. It was shown that atorvastatin increased PON1 activities in different clinical and experimental studies, in line with our study (28)(29)(30)(31)(32), whereas some others failed to find any changes in serum paraoxonase activity following simvastatin or atorvastatin administration (16). Deakin et al (33) explained that patients with the -108C allele, who already have higher PON1 levels, may further benefit from treatment with statins, indicating the importance of gene polymorphism among individuals.…”
Section: Discussionsupporting
confidence: 89%
“…More recently, statins have been reported to reduce DNA damage in vitro and also in vivo, after a variety of insults. There are multiple mechanisms by which statins might reduce DNA damage, including reduction of oxidative stress, [12][13][14][15] inhibition of prenylation of proteins involved in inducing DNA damage, 16 and inhibition of downstream signaling from damaged DNA. 17,18 We, therefore, examined the effect of statin treatment on DNA damage and repair pathways in human VSMCs.…”
mentioning
confidence: 99%